A goal-setting intervention with motocross racers : a case study investigating the effects of an intervention on perceived motivation, confidence, and self-efficacy - Fleming, Tracey Laura (Rhodes University, Faculty of Humanities, Department of Psychology, 2014)
This study aimed to investigate the effects that a specifically tailored goal-setting program would have on two motocross racers in terms of their self-efficacy and motivation, as well as the process of designing this intervention. This case-study approach involved a mixed methods approach, consisting of pre-intervention and post-intervention assessments, interviews, and performance profiles. The tools used include Vealey's (1986) Competitive Orientation Inventory (COI), Gill and Deeter's (1988) Sport Orientation Questionnaire (SOQ), performance profiles, and semi-structured interviews. The goal-setting intervention lasted a total of five weeks. The results from the preintervention and post-intervention assessments were compared to determine whether any changes in motivation or self-efficacy occurred during the intervention. For the first participant, significant changes in both motivation and self-efficacy were present in addition to significant changes in competitive orientation. For the second participant, there were no significant changes in either motivation or self-efficacy. However, for the second participant there was also no change in competitive orientation. Findings suggest that the focus and competitive orientation of an athlete have a significant influence on the types of goals set, and consequently on positive changes in motivation, confidence, and self-efficacy. The influence of the competitive orientation in athletes also highlighted the importance of attaining a balance between performance and outcome goal-related activities. It was also discovered through qualitative assessment that this program is suitable for particular groups of athletes such as those who are injured, display an external locus of causality or are otherwise not performing at their prime.
Keywords: Motocross -- Psychological aspects -- Research; Motorcyclists -- Psychological aspects -- Research; Goal (Psychology) -- Research; Competition (Psychology) -- Research; Motivation (Psychology) -- Case studies; Confidence -- Case studies; Self-efficacy -- Case studies; Sports -- Psychological aspects